FLOOD BASALTS AND LUNAR PETROGENESIS - O'Hara M.J. (My University, 2000)
The popular interpretation of lunar maria, as sequences of primary picritic flood basalts derived by remelting a mantle that had accumulated from a global magma ocean, has many unsatisfactory aspects. The expertise of Keith Cox would have been valuable in their interpretation.